1988
DOI: 10.1002/elps.1150090923
|View full text |Cite
|
Sign up to set email alerts
|

Subtyping of group specific component (GC) in human semen, blood and vaginal fluid by isoelectric focusing in immobilized ph gradients

Abstract: The group specific component (GC) is stable and well suited for forensic casework. Isoelectric focusing of common GC variants from semen, seminal fluid, vaginal fluid and semen stains, on Immobiline DryPlates, pH 4.5-5.4, is of practical value in criminal investigations of sexual deliquencies. GC is present in normospermia and azoospermia seminal fluids and found in about 20% of the vaginal secretions. The GC patterns observed were similar and in accordance with the bands of the individual GC type in plasma/se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The same advantages are observed for GC, the range of choice being pH 4.6-5.3 according to [9]. I F and 1s have a double-band pattern, while the allele GC"2 has a singleband pattern.…”
Section: Proteinsmentioning
confidence: 59%
“…The same advantages are observed for GC, the range of choice being pH 4.6-5.3 according to [9]. I F and 1s have a double-band pattern, while the allele GC"2 has a singleband pattern.…”
Section: Proteinsmentioning
confidence: 59%
“…Gc subtypes have been identified by isoelectric focusing (355)(356)(357)(358)(359). Isoelectric focusing of Gc was reported for semen, blood, and vaginal fluid (396,397). Isoelectric focusing methods for Hp typing have been described (360,361), as well as a micromethod for phenotyping Hp in bloodstains (362).…”
Section: Forensic Biochemistrymentioning
confidence: 99%
“…Using isoelectric focusing on ultrathin immobilized pH gradient gel, Pflug etaf. [3], Pflug [4] and Potsch-Schneider and Klein [5] demonstrated GC subtypes also in semen and seminal stains. We have recently observed that much better isoelectric focusing patterns of GC in human semen can be obtained by treating the samples with neuraminidase.…”
Section: Introductionmentioning
confidence: 99%